Evaluating Strategies for Enhancing Medication Adherence in the Kingdom of Saudi Arabia (KSA): A Cross-Sectional Study - Alhomoud FK; Alwohaibi LW; Aljarrash K; Alhomoud F; Alamer K; Alsultan MM; Alqarni Y; Alotaibi N; Alsaad AK; Alqahtani AD; Alkhnbashi RS (Patient Preference and Adherence)
Farah Kais Alhomoud,1 Lama Wesam Alwohaibi,1 Kawthar Aljarrash,1 Faten Alhomoud,1 Khalid Alamer,1 Mohammed M Alsultan,1 Yousef Alqarni,1 Noor Alotaibi,1 Anwar Khalifah Alsaad,1 Afrah Dhafer Alqahtani,1 Reem Saad Alkhnbashi2 1Department of Pharmacy Practice, College of Clinical Pharmacy, Imam Abdulrahman Bin Faisal University, Dammam, Kingdom of Saudi Arabia; 2The Pharmacy Cardiology Department, King Fahad General Hospital, Jeddah, Kingdom of Saudi ArabiaCorrespondence: Farah Kais Alhomoud, Department of Pharmacy Practice, College of Clinical Pharmacy, Imam Abdulrahman Bin Faisal University, King Faisal Ibn Abd Al Aziz road, Dammam, 34212, Kingdom of Saudi Arabia, Tel +966133335547, Email fkalhomoud@iau.edu.saPurpose: This study aimed to assess medication adherence strategies among users in Saudi Arabia, explore the prevalence and effectiveness of behavioral, technical, and organizational tools, and identify key predictors of adherence related to demographic, health, and medication characteristics.Patients and Methods: A descriptive cross-sectional study was conducted among 250 Saudi residents aged ≥ 18 who regularly take prescription/non-prescription medications. The questionnaire was developed through a literature review, validated by academic pharmacists, and refined based on pilot testing feedback. A convenience sampling method, complemented by snowball sampling, was employed to recruit participants. Limitations like sampling bias and self-reported data emphasize the need for broader studies. Quantitative analysis was performed using IBM SPSS.Results: Participants were predominantly young adults (84%) and females (84%), with 54% reporting being healthy and 46% managing chronic conditions. Behavioral strategies, such as time-based reminders, were the most commonly used (40%), followed by technical tools (33%), including mobile applications. Employment status significantly influenced adherence, with employed individuals (adjusted OR: 3.274, p = 0.028) and those working > 8 hours daily (adjusted OR: 9.838, p = 0.049) exhibiting higher adherence. Fieldwork negatively impacted adherence (adjusted OR: 0.052, p = 0.007). While other demographic and health factors showed no significant associations, trends suggested that complex medication regimens increased the likelihood of using adherence strategies.Conclusion: Behavioral strategies, such as time- and location-based reminders, and technical tools, like apps, effectively improved medication adherence. Healthcare providers should promote simple, cost-effective methods, such as pillboxes and mobile reminders, tailored to patient needs. Addressing adherence barriers for individuals with demanding/unexpected schedules or complex regimens through targeted interventions and awareness campaigns is essential. Future research should explore these strategies’ scalability and long-term impact in diverse healthcare settings.Keywords: health behavior, medication adherence, medication therapy management, patient compliance